A Flexible Concentric Circle Structured Zinc‐Ion Micro‐Battery with Electrodeposited Electrodes. Issue 9 (9th August 2020) - Li, Rui; Li, La; Jia, Rui; Jiang, Kai; Shen, Guozhen; Chen, Di
Abstract: High‐performance all‐solid‐state rechargeable batteries with highly wearable, deformable, and waterproof features have attracted considerable attention for their promising applications in next‐generation wearable electronics. Herein, a flexible all‐solid‐state in‐plane Zn‐polyaniline (PANI) micro‐battery with concentric circle structure is reported by directly electrodepositing both positive and negative electrode materials on tyrene‐isoprene styrene rubber (SIS) substrate. As‐fabricated battery delivers a high specific area capacity of 250 µAh cm −2, a high energy density (0.25 mW h cm −2 ) and a high power density (0.99 mW cm −2 ) as well as excellent cyclin stability (68% capacity retention after 1200 cycles). More importantly, the concentric circle structured micro‐battery exhibits superior mechanical flexibility, reasonable stretchability, outstanding waterproof ability, and temperature resistance up to 80 °C and excellent integratability with wireless charging coils. Abstract : A flexible Zn‐PANI micro‐battery with concentric circle structure is fabricated using porous Zn microrods and PANI nanorods as electrode materials, which exhibits high energy/power densities, superior high cycling stability, mechanical flexibility, outstanding waterproof ability, and excellent integratability of assembling with wireless charging coils to form integrated system.